Sieben neue Pseudopsis-Arten aus China mit einer Bestimmungstabelle der paläarktischen Arten (Coleoptera: Staphylinidae, Pseudopsinae). Beiträge zur Kenntnis der ostpaläarktischen Insekten (7). - Zerche, Lothar (Contributions to Entomology = Beiträge zur Entomologie, 1998)
The genus Pseudopsis Newman is reported from China for the first time. Seven new species are described and compared with related or similar species: puetzi sp. n. [Shaanxi]; yunnanensis sp. n. [Yunnan]; gonggaensis sp. n., smetanai sp. n., schuelkei sp. n., hermani sp. n. [all Sichuan]; gansuensis sp. n. [Gansu]. For the new species the aedeagus and the longitudinal carinas of the pronotum are figured. A key to all 20 Palaearctic species is given. Nomenclatural Acts gansuensis Zerche, 1998 (Pseudopsis), spec. n. gonggaensis Zerche, 1998 (Pseudopsis), spec. n. hermani Zerche, 1998 (Pseudopsis), spec. n. puetzi Zerche, 1998 (Pseudopsis), spec. n. schuelkei Zerche, 1998 (Pseudopsis), spec. n. smetanai Zerche, 1998 (Pseudopsis), spec. n. yunnanensis Zerche, 1998 (Pseudopsis), spec. n.